2018
DOI: 10.3389/fphys.2018.01500
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemia-Induced Arrhythmias and Heart Failure: New Insights and Implications for Therapy

Abstract: Routine use of diuretics and neurohumoral activation make hypokalemia (serum K+ < 3. 5 mM) a prevalent electrolyte disorder among heart failure patients, contributing to the increased risk of ventricular arrhythmias and sudden cardiac death in heart failure. Recent experimental studies have suggested that hypokalemia-induced arrhythmias are initiated by the reduced activity of the Na+/K+-ATPase (NKA), subsequently leading to Ca2+ overload, Ca2+/Calmodulin-dependent kinase II (CaMKII) activation, and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 137 publications
(174 reference statements)
0
72
0
10
Order By: Relevance
“…The physiological significance of such pools of Na ϩ is currently unknown, but differential regulation of Na ϩ -dependent processes in distinct compartments allows fine tuning of intracellular processes such as contractility and pH regulation. Several publications have showed that the specific intracellular colocalization of NKA and NCX facilitates tight regulation of cardiac contractility and relaxation (16,21,36) and arrhythmic susceptibility (33). In addition, since the subsarcolemmal space constitutes only a fraction of the total cell volume, less Na ϩ needs to be cycled across the sarcolemma to achieve a large physiological effect, which likely promotes thermodynamic efficiency.…”
Section: Nka-sensed [Na ϩ ] Is High Compared With the Bulk Cytosolmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological significance of such pools of Na ϩ is currently unknown, but differential regulation of Na ϩ -dependent processes in distinct compartments allows fine tuning of intracellular processes such as contractility and pH regulation. Several publications have showed that the specific intracellular colocalization of NKA and NCX facilitates tight regulation of cardiac contractility and relaxation (16,21,36) and arrhythmic susceptibility (33). In addition, since the subsarcolemmal space constitutes only a fraction of the total cell volume, less Na ϩ needs to be cycled across the sarcolemma to achieve a large physiological effect, which likely promotes thermodynamic efficiency.…”
Section: Nka-sensed [Na ϩ ] Is High Compared With the Bulk Cytosolmentioning
confidence: 99%
“…In contrast, Na ϩ removal by NKA may create local Na ϩ coldspots. Indeed, the ␣ 2 -isoform of NKA regulates [Na ϩ ] sensed by NCX, thereby regulating contractility (1,16,36) and cardiac arrhythmogenesis (33). However, the properties of subsarcolemmal [Na ϩ ] apparently diverge when different Na ϩ transporters are studied.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, plasma potassium levels range from 3.5 to 5.5 mEq/L, and the risk of arrhythmia increases at values below 2.7 mEq/L . In acute experimental models in healthy rat hearts, the potassium level is reduced to 1 mEq/L .…”
Section: Introductionmentioning
confidence: 99%
“…During the course of the disease, both the husband and the wife had obvious hypokalemia, and the wife had a brief premature heart beat. Hypokalemia is easy to induce arrhythmia and heart failure [12][13][14][15][16] , even related to some malignant arrhythmias 17 , especially for patients with basic heart disease.…”
Section: Discussionmentioning
confidence: 99%